Underperforming Academic Scholars Rostered in the Pipeline to Prison or Nowhere on a Lifeline! (Journal of Advanced Research in Leadership, 2025)
This study examined the extent to which one of the Department of Education’s (DOE) Coordinated Early Intervening Services (CEIS) affects academically struggling general education students from various elementary, middle, and high schools in Equliebeh School District. This study utilized quantitative techniques to examine whether CEIS participation impacted KDG–12 scholars’ academic growth, behavioral indicators, and demographic group representation in eligibility for Individual Education Plans (IEPs). It employed a causal-comparative design, grounded in a positivist paradigm, and examined how English Language Arts (ELA) and Math scores, absences, suspensions, and school mobility affected the academic performance of 395 scholars over a 24–27-month period. The findings from this study provided valuable insights into the role of demographics in the eligibility for and enrollment in the CEIS program. Ethnicity played a significant role in a student's likelihood of enrolling in the program, as indicated by all p-values < 0.001. Grounded in Bandura’s Self-Efficacy Theory, the study examined how scholars’ motivation, resilience, and perceived ability to succeed may have influenced CEIS outcomes, particularly among ethnic groups that are overrepresented in program enrollment. Furthermore, the study highlighted disparities among diverse racial and ethnic groups, thus aligning with the tenets of academic inequities. These disproportions underscore the urgency of addressing structural and systemic barriers that perpetuate educational inequities before, during, and after intervention. The findings emphasize the importance of fidelity monitoring, culturally responsive pedagogy, and trauma-informed support to ensure CEIS aligns with its federally mandated equity objectives.